The Implementation of Policy on Appointment of Permanent Lecturers at Private Universities in the City and Regency of Cirebon - Nursahidin; Soleh Suryadi; Ali Anwar Yusuf (GoAcademica Research & Publishing, 2020)
The focus of this research is the implementation of policy on the appointment of permanent lecturers at private universities in the City and Regency of Cirebon which are not optimal yet,so that Private Universities in the City and Regency of Cirebon are faced with various problems in the appointment of permanent lecturers, that is, they have not yet fully paid attention to the regulations and quality standards of lecturers. The sub focus of this research is application of the approach of the idealized policy, the implementing organization, the target group and environmental factors as dimensions of policy implementation in relation to the appointment of permanent lecturers at private universities in the City and Regency of Cirebon.Based on the problem statement set out at the focus of research,then downgraded into a research question, what are the factors that have caused the implementation of policy on the appointment of the permanent lecturers at Private Universities in Cirebon City and Regency to be not yet optimal? What efforts are made by private universities in the city and regency of Cirebon to appoint permanent lecturers?And what strategies are effective to optimize the implementation of the policy of appointment of the permanent lecturers at Private Universities in the City and Regency of Cirebon?The results of the researchthen further analyzed with the theory of organizational effectiveness with the criteria of production, efficiency, satisfaction, adaptation and development. The method used in the research is a qualitative research method.Qualitative data collection is done through observation, interviews and Focus Group Discussion (FGD).In this research the writers describe the phenomena found in the field related to the research problem, then analyze it but without calculating the effect of a variable to other variables.Through this qualitative research method, it is expected that the writers can obtain accurate data related to the problem under research, so that the writers can analyze it in depth on how to implement the policy of appointment of permanent lecturers at PTS (Private Universities) in the City and Regency of Cirebon. The results showed the findings in the form of developing theories that strengthen the concept of Smith's policy implementation process (1973) that optimizing the appointment of permanent lecturers at Private Universities in the City and Regency of Cirebon can be achieved if Organizational Culture, Motivation and Competitiveness are developed.